TRANSFORMATION OF LMS-BASED LEARNING EVALUATION MANAGEMENT TO IMPROVE STUDENT ASSESSMENT ACCOUNTABILITY - Wafi Bahrul Ilmi; Moh. Ainul Yaqin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the application of Learning Management System (LMS)-based learning evaluation management in improving student grade accountability. This study uses a qualitative approach with a literature study method to examine the concept, strategy, and implementation of LMS-based learning evaluation management. Data were obtained from various scientific literature, including journal articles, books, proceedings, and relevant scientific documents. Data were analyzed interactively through data reduction, data presentation, and conclusion drawing, and validated using source triangulation to ensure the credibility and objectivity of the study. The results of the study indicate that LMS-based evaluation management, which includes digital question bank planning, synchronized online exam implementation, and automatic grade processing, can minimize human error and subjectivity in the assessment process. The digital footprint feature in the LMS provides authentic evidence of student learning activities and evaluation implementation. In addition, the transparency of assessment results that can be accessed by students and parents contributes to increasing public trust and accountability of educational institutions. The integration of LMS in learning evaluation governance not only encourages the digitalization of the assessment process but also transforms the evaluation system to be more credible, transparent, and accountable. This research recommends strengthening educators' digital capacity, standardizing technology infrastructure, and developing LMS-based evaluation policies as strategies to optimize educational quality in the era of digital transformation.